Karakteristik Energi Limbah Tebangan Jati Klonal dari Paliyan-Gunungkidul - Denny Irawati; Aditya Nur Cahyo; Yusi Dian; Joko Sulistyo; Sigit Sunarta; Rini Pujiarti; Ganis Lukmandaru; Johanes Pramana Gentur Sutapa (Faculty of Forestry Universitas Gadjah Mada, 2023)
Breeding teak with a clonal system was a common practice to enhance productivity and reduce rotation. A private company in Paliyan Sub-District, Gunungkidul Regency, Indonesia, developed Jati Unggul Nusantara (JUN) through vegetative propagation, particularly cloning, using cuttings. JUN had gained widespread popularity as a replacement for conventional teak varieties for commercial purposes. The utilization of JUN commercial timber left various non-commercial biomass forms, such as leaves, branches, and twigs. This research aimed to assess JUN logging waste biomass's energy potential and characteristics across different tree-age stands. This research used non-commercial biomass from six- and eight-year-old trees, including branches, twigs, leaves, stumps, and unmerchantable top stems. The results showed that the average dry weight of JUN logging waste from six- and eight-year-old trees was 31.5 and 53.5 kg/tree, while the calorific value ranged from 4516.4–5177.7 cal/g. This waste had good characteristics as an energy material, specifically from the part of unmerchantable top stems with a high fuelwood value indexof 6579.6.